Serum miR-885-5p can be used as a marker for efficacy prediction and prognosis of advanced liver cancer - Wang, Kai (Cellular and Molecular Biology, 2020)
This study set out to observe the value of miR-885-5p in the prognosis evaluation of liver cancer patients after transcatheter arterial chemoembolization. Sixty liver cancer patients treated in Zhuji City People's Hospital between January 2019 and September 2019 were enrolled. The patients were categorized into survival (SG) and death groups (DG) according to prognosis. Sixty-five healthy individuals were included as a control. The expression of miR-885-5p and miR-21were measured by the qRT-PCR and predictive value of diagnostic efficiency was determined by the ROC curve. Multivariate Cox regression analysis was performed to explore independent risk factors. Results showed that levels of miR-885-5p in the serum of liver cancer patients were obviously lower than that of the control group; however, levels of miR-21 in the serum of liver cancer patients were higher than that of healthy individuals. Patients with miR-885-5p low expression and miR-21 high expression had poor differentiation, stages III+IV, and their incidence of lymphatic invasion and distal metastasis was higher (P<0.05). AUC values of miR-885-5p and miR-21 single diagnosis were both > 0.8. The relative level of miR-885-5p in the serum of the SG was dramatically higher than that of the DG, and its relative level of miR-21 in serum was significantly decreased compared with DG. ROC curves in diagnosing the prognosis of liver cancer patients were drawn, AUC values of serum miR-885-5p and miR-21 in diagnosing their prognosis were both > 0.8. Cox regression analysis was carried out on independent factors affecting their prognosis. The results revealed that the TNM stage, lymphatic invasion, distal metastasis and miR-885-5p were independent prognostic factors affecting their 5-year survival. It was concluded that miR-885-5p exhibited the potential to be a serum biomarker to evaluate the efficacy of advanced liver cancer.